2021
DOI: 10.3390/ijms22168997
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Lipids in Saliva, Tears and Minor Salivary Glands of Sjögren’s Syndrome Patients Using an HPLC/MS-Based Approach

Abstract: The diagnostic work-up of primary Sjögren’s syndrome (pSS) includes quantifying saliva and tear production, evaluation of autoantibodies in serum and histopathological analysis of minor salivary glands. Thus, the potential for further utilizing these fluids and tissues in the quest to find better diagnostic and therapeutic tools should be fully explored. Ten samples of saliva and tears from female patients diagnosed with pSS and ten samples of saliva and tears from healthy females were included for lipidomic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 47 publications
0
10
0
2
Order By: Relevance
“…Sekiguchi [ 140 ] showed that the signaling of the S1P receptor 1 (S1P 1 ) may in fact modulate autoimmune phenotypes in pSS, through the immune and epithelial cells. Moreover, another case-control study [ 139 ] revealed differences in the lipidomic profiles of tears and saliva in patients with pSS compared to healthy controls, involving 29/86 individual lipid species.…”
Section: Evidence Regarding Ceramides In Patients With Airdsmentioning
confidence: 99%
“…Sekiguchi [ 140 ] showed that the signaling of the S1P receptor 1 (S1P 1 ) may in fact modulate autoimmune phenotypes in pSS, through the immune and epithelial cells. Moreover, another case-control study [ 139 ] revealed differences in the lipidomic profiles of tears and saliva in patients with pSS compared to healthy controls, involving 29/86 individual lipid species.…”
Section: Evidence Regarding Ceramides In Patients With Airdsmentioning
confidence: 99%
“…Among the proteins detected are growth factors [ 16 , 17 ], cytokines [ 18 ], matrix metalloproteinases [ 19 ], immunoglobulins [ 20 , 21 , 22 , 23 ], sex hormones [ 24 , 25 , 26 , 27 , 28 ], proteases and protease inhibitors [ 29 , 30 , 31 , 32 , 33 ], calcium-binding proteins [ 34 , 35 ], and glycoproteins [ 36 , 37 , 38 ]. The tear film lipid layer (TFLL) acts as an interface between the aqueous layer and air and is the composition of different types of lipids, including cholesteryl esters (CE), wax esters (WE), and triacylglycerol (TAG) [ 17 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. In tears, circulating microRNAs (cimiRNAs) as potential biomarkers were also found [ 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…In its application in DED, ML has largely been used for image analysis from slit lamp examinations 15 , meibography 16 , and in vivo confocal microscopy 17 , as well as a few studies concerning osmolarity 18 , and proteomic analysis 19 . Additionally, our group recently employed dimensionality reduction through principal components analysis to compare salivary and ocular lipids and lipidomic profiles in patients with Sjögren`s syndrome to healthy controls 20 . There is no definitive test for DED, and patients must undergo several and occasionally unpleasant clinical examinations demanding a great deal of time and resources.…”
Section: Introductionmentioning
confidence: 99%